That mutant called "text" (2006)
Exploring emergent dimensions of the "text" in the new media is the primary concern of this paper. The continually changing context of cultural, artistic, aesthetic, and literary production makes it imperative to re-examine traditional concept of (the) text (oral and written), and its mutations. More precisely, orality in contemporary Africanist scholarship is a discursive formation; it is a site of ideological struggle for self-representation and self-reinscribing in contesting foisted privileging norms and narratives. The paper draws attention to those normative assumptions of what constitute literature and the theoretical guide that has engendered the shaping of the discipline. In this case, the enquiry deepens further by examining some existing undercurrent layers of written literature in oral narrative and performance, and the consequent transpositions that mediate it through the new media made possible by the electronic technology.